TP53 Mutation as Molecular Marker in the Assessment of Surgical Margin Status in Head and Neck Squamous Cell Carcinoma - Rayamajhi, Asmita; Acharya, Bibek; Khanal, B. (Nepalese Journal of Cancer, 2021)
Genetic alteration of tumor suppressor and oncogene plays important role in development and progression of cancer. Tumor suppressor gene, Tp53 also knows as ‘guardian of genome’ has very important role in head and neck squamous cell carcinoma (HNSCC). Mutation of Tp53 has been commonly observed in other carcinomas including HNSCC, comprising of 75-85% of head and neck cancer, with highest in larynx and hypopharynx followed by oral cavity. Tp53 mutation is more commonly seen in Human Papilloma Virus (HPV)-ve and wild type Tp53 in HPV+ve carcinomas. Role of Tp53 mutation help us to know about the prognostic state, molecular stage and chance of local recurrence. Different studies have highlighted the importance of assessing Tp53 mutation in the negative surgical margin, which showed mutation of Tp53 in the negative surgical margin resulted increase in chance of local recurrence. These studies provide significance of moving conventional method of histopathological assessment to molecular assessment, that gives advantage of proper management decision as well as prognosis of tumor. Regarding techniques of these assessments, molecular technique has been always superior to immunohistochemistry (IHC) but is somewhat tedious, so more clinical analysis on the alternatives of IHC combined with Next generation sequencing (NGS) gives the platform to perform more Tp53 mutation test in the surgical margin. This is the need of time to incorporate molecular staging in the conventional staging for proper treatment and outcome in the management of head and neck cancers.